2022
DOI: 10.1002/jocb.545
|View full text |Cite
|
Sign up to set email alerts
|

How Creative Self‐Concept Leads to Happiness: A Multilevel Chain Mediating Model

Abstract: Recent research has shown that creative self‐concept might be not only a path to people's creativity but also a path to their positive affect. This study proposed and examined the underlying mechanisms of how creative self‐concept is associated with positive affect through the mediating role of people's daily creative behavior and creative self‐assessment. We recruited 101 Chinese undergraduate students to report their creative behavior, creative self‐assessment, and experiences of positive emotion states each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Since the creative self-concept, which includes creative personal identity, refers to one’s understanding of how able they are to think and act creatively ( Karwowski and Beghetto 2019 ), one may suppose that the rate at which creators engage with the contexts they find themselves in may impinge on the quantity and quality of activities related to little-c/everyday creativity and mini-c creativity. Supporting this argument is a recent study by Li et al ( 2022 ). The authors investigated the link between the creative self-concept, and creative behaviour amongst others and found a positive relationship between the two.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…Since the creative self-concept, which includes creative personal identity, refers to one’s understanding of how able they are to think and act creatively ( Karwowski and Beghetto 2019 ), one may suppose that the rate at which creators engage with the contexts they find themselves in may impinge on the quantity and quality of activities related to little-c/everyday creativity and mini-c creativity. Supporting this argument is a recent study by Li et al ( 2022 ). The authors investigated the link between the creative self-concept, and creative behaviour amongst others and found a positive relationship between the two.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…Our study demonstrated that creativity predicted subsequent willpower self-efficacy, with no evidence for the reverse. Yet of course, the decision to engage in creative activity in the first place likely requires willpower-related attributes such as motivation and creative self-efficacy (Li et al, 2022). Indeed, creative activities themselves often require self-regulatory effort to translate into creative achievements (Ivcevic & Nusbaum, 2017; Zielińska et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological Momentary Assessment (EMA) and daily diary studies are excellent methods for examining relationships between variables in daily life (Shiffman et al, 2008). For example, higher perceived creativity is associated with greater positive affect (Li et al, 2022). Additionally, lagged analyses from EMA data allow for examination of the effects of one variable on another at a subsequent timepoint, and positive affect at one time point has predicted subsequent creativity in several studies (Amabile et al, 2005; Chi et al, 2021; Karwowski et al, 2017; To et al, 2012).…”
Section: Established Links Between Creativity and Affectmentioning
confidence: 99%